A comparative study of two selected restaurants in the University of the Philippines Diliman campus - Carreon, Carmelo Hokson (2007)
This paper aimed to study two restaurants in the University of the Philippines, Diliman campus. The study determined which of the two restaurants were successful in translating their image to the public and how they were able to execute their desired image to the public. Research data was gathered through observations, interview, and survey questionnaires. A total of 38 respondents from within the university campus were involved in the study. The data gathered were correlated with the elements of interior design and theories on restaurant design and food service management. The results of the study showed that Restaurant B was more successful in translating their image to their market than Restaurant A. It was identified that the consistent use of elements of design pertinent with their "ruined" image was well recognized by their market. Major findings show that the success of a restaurant's image rely on the consistent interpretation in all aspects of design. Restaurant B was consistent in applying their "ruined" image in the interior and exterior of their establishment. On the other hand, Restaurant A was amiss in applying their designs in some areas thus comprising the effectivity of their image. Moreover, the study established that a more straightforward "casual" image was more easily identified by the respondents while a hidden "ruined" image was more difficult to perceive and subject to different interpretations. Overall, the consistency in design of Restaurant B is what made the translation of their image to their public a success.